A Conceptual Review Paper: Revisiting the Non-linear Relationship Between Dividend and Firm Value in Shariah and Non-Shariah Compliant Firms - Bakri, Mohd Ashari; Nasir Samsulbahri, Mohd; Isa Abd Jalil, Mohamad; Ahsan, Md Hafizi; Chia Yong, Chia (Suhuf: International Journal of Islamic Studies, 2024)
In the modern corporate world, dividend policy is a widely discussed topic. Early academic literature mainly focused on the linear relationship between dividends and firm value. However, a non-linear (J-shaped) relationship was later discovered in major economies, indicating that firm value may have a more complex connection to dividends. This study reviews existing literature on the non-linear relationship between dividends and company value, suggesting that this relationship might also exist between Shariah-compliant and non-Shariah-compliant firms. The low leverage characteristic of Shariah-compliant firms may contribute to this potential relationship. An extensive search through Google Scholar and Scopus revealed that few empirical studies have examined this non-linear relationship. Notably, no analysis has yet investigated the non-linear relationship between dividends and firm value specifically among Shariah-compliant firms. This article provides a conceptual overview of how and why such a relationship may exist. The review highlights the need for further research, offering insights that could help policymakers and firms make informed decisions to enhance firm performance.